Weighted kappa as a function of unweighted kappas. Issue 5 (28th May 2017) - Moradzadeh, N.; Ganjali, M.; Baghfalaki, T.
ABSTRACT: The kappa coefficient is a widely used measure for assessing agreement on a nominal scale. Weighted kappa is an extension of Cohen's kappa that is commonly used for measuring agreement on an ordinal scale. In this article, it is shown that weighted kappa can be computed as a function of unweighted kappas. The latter coefficients are kappa coefficients that correspond to smaller contingency tables that are obtained by merging categories.